Analisis Pengaruh Jumlah Objek Wisata, Wisatawan, Hotel dan Akomodasi Terhadap Pendapatan Asli Daerah di Kabupaten Samosir Tahun 2017-2021 - Benyamin Maduwu; Viona Nadya Thabita Pangaribuan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this study is to know the impact of the number of tourist attractions, the number of tourists, and the number of hotels and accommodations on native incomes in samosir 2017-2021. The data used is secondary data obtained from statistics from samosir district. Data collected from 2017 to 2021. Data is processed using the eviews program. Based on these conclusions, Suggestions have been suggested that governments should be able to increase facility building to its level, and promote systems that increase the number of tourist attractions, the number of tourists and the number of hotels to raise native income in samosir districts.